INITIATING PAULO FREIRE'S PERSPECTIVE ON THE EDUCATIONAL PARADIGM IN THE INDEPENDENT LEARNING CURRICULUM AND ITS RELEVANCE TO ISLAMIC EDUCATION IN MADRASAH - Taufiqurrohman, Ofik; Misbahuddin, Misbahuddin; Wasehudin, Wasehudin (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This research explores Paulo Freire's perspective on Islamic education and its relevance to the Islamic curriculum in madrasahs in prioritizing moral and ethical values. This report uses a comprehensive approach to analyze Freire's 1972 book, "Pedagogy of the Oppressed" and highlights the importance of Freire's paradigm in Islamic education in Indonesia, especially in madrasah. This paradigm emphasizes the importance of student involvement, active participation, and participation in learning, in line with the objectives of the Islamic curriculum to create critical, creative, and responsible individuals in the 21st century. Integrating Islam into Freire's paradigm can also improve character, morals, and religious values in education. It emphasizes dialogue, participation, and contextual engagement in learning, fostering a sense of responsibility for developing skills and values relevant to the social and cultural context. It is hoped that applying the Freire paradigm and Islamic education in Indonesian education, especially in madrasahs, will lead to a more comprehensive, inclusive, and meaningful education.